Penerapan Metode Fuzzy Mamdani Dalam Menentukan Persediaan Beras Tahun 2023 - Yeni Sinaga; Debora Exaudi Sirait; Juli Antasari Sinaga (CV Putra Publisher, 2023)
Indonesia is an agricultural country that relies heavily on agriculture, especially the production of rice as a staple food. The government has an important role in maintaining food security through the Logistics Affairs Agency (BULOG). Perum BULOG must anticipate uncertainty in rice demand and ensure sufficient stock. Fuzzy logic methods, especially the Mamdani Method, are used to optimize rice supplies. This research is a quantitative approach with descriptive methods, describing the characteristics of the research object without relationships or comparisons with other variables. Fuzzy logic methods, especially the Mamdani Method, are used to optimize rice supplies. This research aims to apply the Fuzzy Mamdani Method in determining the amount of rice inventory at Perum BULOG on Jl. Asahan.The centroid method is used to calculate z values ​​based on the results of rule aggregation. So, the z value (inventory) based on the Mamdani method with input x 10044820 and y 936000 is 805086. The results of this defuzzification indicate that inventory is